Reservoir host immunology and life history shape virulence evolution in zoonotic viruses - Brook, Cara E.; Rozins, Carly; Guth, Sarah; Boots, Mike (PLOS Biology, 2023)
Bats are natural reservoir hosts for viruses that cause higher case fatality rates in humans than do zoonoses derived from any other source. This study builds a nested within-host, population-level model to offer a mechanistic explanation for this phenomenon.